Modern Czech theatre : reflector and conscience of a nation - Burian, Jarka, 1927-2005 (Studies in theatre history and culture., 2000)
The story of Czech theatre in the twentieth century involves generations of mesmerizing players and memorable productions. Beyond these artistic considerations, however, lies a larger story: a theatre that has resonated with the intense concerns of its audiences acquires a significance and a force beyond anything created by striking individual talents or random stage hits. Amid the variety of performances during the past hundred years, that basic and provocative reality has been repeatedly demonstrated, as Jarka Burian reveals in his extraordinary history of the dramatic world of Czech theatre.